Systems Approach to Disaster Risk Reduction in Comprehensive Land Use Planning of San Jose City, Nueva Ecija, Philippines - Abella, Gella Patria L.; Lansigan, Felino P.; Tubay, Jerrold M.; Carmona, Ana Rosa A. (Journal in Urban and Regional Planning; Vol 4 No 1 (2017): Journal in Urban and Regional Planning, 2021)
In the Philippines, mainstreaming disaster risk reduction (DRR) in the development plans of local government units (LGUs) was emphasized in Republic Act 10121, in response to the Hyogo Framework of Action. In this study, the methodological framework of integrating DRR in the comprehensive land use plan (CLUP) using a systems approach was developed and operationalized using the case of San Jose City, Philippines. In the Geographic Information Systems (GIS)-assisted analysis, the city’s land area was divided into 1-hectare (ha) by 17,203 grids. Five land use types, namely: tomato, bitter melon, rice, onion, and residential areas, were reviewed in terms of vulnerability using multiple goal linear programming (MGLP). The disaster risk of the city, as a function of hazard, exposure, and adaptive capacity, was assessed using climate scenarios for 2035 along with extreme events on flooding, drought, rain-induced landslides, and earthquake. The city registered mean scores of exposures (2.74), susceptibility (3.69), and lack of adaptive capacity (2.52), as well as a mean vulnerability index of 11.02, which is relatively low compared to the highest possible score of 25. The hazard susceptibility score is expected to increase from 1.18 under the current condition to 1.42 under the 2035 scenario. Consequently, the disaster risk is expected to increase from 12.98 to 15.6 within the same period. Areas along the river network scored higher in terms of hazard. Under the current and 2035 scenarios, target crop production for selected crops – rice, onion, tomato, and bitter melon – is predicted to be met with the potential to increase farmers’ net income based on the proposed land use allocation. Moreover, the allocation can minimize the disaster risk of the city to 0.53 and 1.45, meeting the demand for safe residential areas of 567.87 ha in the current scenario, and 970.05 ha based on predicted population growth rates for the 2035 scenario. A systems approach is vital in optimizing land use allocation considering development goals and disaster risks of LGUs.
Keywords: optimal land use allocation, disaster risk reduction, vulnerability, hazard